Overlooked Pneumonia-Like Lung Cancer with Elevated Neutrophils and Typical Pneumonia Imaging findings - Mao, Xuan M; Guo, Ai J; Yuan, Xin H; Cui, Ming Y; Zhang, Di; Ge, Yan L; Sun, Guo G (Clinical laboratory (Heidelberg), 2025)
Pneumonia-type lung cancer is a specific type of lung cancer with low incidence, lack of clinical specificity, and strong imaging similarity to pneumonia, which can be easily misdiagnosed as a lung infection. We report a special case of a patient who was misdiagnosed as Mycoplasma pneumonia by routine blood tests, bronchoscopy, NGS of alveolar lavage fluid and combined with the patient's lung CT imaging features, and then was definitively diagnosed as lung adenocarcinoma by percutaneous lung puncture. The patient's solid shadow in the right lower lung remained unabsorbed after aggressive anti-infection, and finally the diagnosis of lung adenocarcinoma was finally clarified by percutaneous lung puncture. In middle-aged and elderly patients with a first diagnosis of lung infection, if the exudate shadow remains unabsorbed after aggressive empirical anti-infective treatment, the infection should be aggressively investigated for specific pathogens such as Mycobacterium tuberculosis, nontuberculous mycobacteria, fungi, adenoviruses, etc., and in addition to that, malignant lesions should also be investigated.